MANTLE HETEROGENEITY FROM TRACE ELEMENTS: MAR TRIPLE JUNCTION NEAR 14°N - Dmitriev L.; Sobolev A.; Bougault H.; Needham H.D.; Schilling J.G.; Joron J.L. (My University, 1988)
The trace element composition of basalts dredged at the axis of the Mid-Atlantic Ridge between 12°N and 17°N by the R/V “Akademik Boris Petrov” demonstrates the presence of a high-amplitude geochemical anomaly, centered around 14°N and extending at least 300 km along the strike of the Rift Valley. The anomaly does not fit easily into any of the models that have been proposed: it may reflect the upwelling of an embryonic mantle plume or of a passive mantle domain responsible for or associated with a triple junction, possibly marking a recent shift into the area of the South American/North American plate boundary.